The Effect of Inaportnet System Implementation and Application Operator Skills on Ship Service Performance at Ciwandan Port, Banten - April Gunawan Malau; Wida Cahyaningrum; Anindya Putri Utami (Dinasti Publisher, 2022)
In supporting the performance of ship services using the inaportnet system at the Port of Ciwandan Banten, there are still many problems that arise in the company related to the implementation of the inaportnet system and operator skills. These problems are the frequent occurrence of system errors when the inaportnet system is being used and the lack of application operator skills in using the inaportnet system, resulting in the ship's service performance being not optimal. Based on these problems, the authors conducted an analysis to determine whether there was an effect of implementing the inaportnet system and application operator skills on the performance of ship services at the Ciwandan Port of Banten. The type of research used is quantitative method. Data collection was carried out by questionnaires which were distributed directly to 60 respondents, namely inaportnet service users in the KSOP Class I Banten working area with a total of 27 statements. In looking for the results of the calculations the author uses the SPSS 26 program and performs several data analyzes, namely: validity test, reliability test, and homogeneity test, correlation coefficient analysis, coefficient of determination analysis, regression analysis, t-test and f-count. Conclusions in this study were carried out by comparing the data obtained from the answers of existing respondents. Based on the acquisition of questionnaire data and data processing, the results showed that the application of the system and operator skills together proved to be positive and significant on the performance of ship services with a calculated F value > F table, which was 85,419 > 3.16. The author describes several solutions to improve the performance of ship services, namely by increasing the performance of the inaportnet system, increasing operator skills by conducting training, and providing competent application operators to maximize company performance.